Kolaborasi Sistem Among dengan Kompetensi Guru Pendidikan Agama Kristen - Oktavianti, Nelci; Sutrisno, Sutrisno; Putrawan, Bobby Kurnia (Sekolah Tinggi Teologi IKAT Jakarta, 2022)
Education in Indonesia now requires competent teachers with the competencies they have. The competencies referred to here are paedagogic, personality, social, professional, and spiritual competencies. The five competencies must be carried out in an integrated manner by the PAK teacher. While the among system can encourage educators to be role models, motivators, and encouragement for students. In the among system, in which there is a philosophy, Ing Ngarsa Sun example, the Madya Mangun Karsa, and Tut Wuri Handayani. Collaborate the competence of PAK teachers with the system. This study was conducted using qualitative methods, through this study we can find out the collaboration between the system with the competence of teacher PAK. So by collaborating the competence of PAK teachers with the among System, teachers are expected to be role models, motivators, facilitators, and responsible for creating generations of believers, free-born, independent, disciplined, intelligent, skilled, and responsible for themselves, their families, and communities. AbstrakPendidikan di Indonesia sekarang sangat memerlukan guru-guru yang kompeten dengan kompetensi yang dimilikinya. Kompetensi yang dimaksud disini adalah kompetensi paedagogik, kepribadian, social, professional dan spiritual. Kelima kompetensi harus dilakukan secara integrasi oleh guru PAK. Sedangkan sistem among dapat mendorong pendidik menjadi teladan, motivator dan pendorong bagi peserta didik. Dalam sistem among, yang di dalam terdapat falsafah, Ing Ngarsa Sun Tuladha, Ing Madya Mangun Karsa dan Tut Wuri Handayani. Mengkolaborasikan kompetensi guru PAK dengan sistem among. Penelitian ini di lakukan dengan menggunakan metode kualitatif, melalui penelitian ini kita dapat mengetahui kolaborasi sistem Among dengan kompetensi guru PAK. Sehingga dengan mengkolaborasikan kompetensi guru PAK dengan sistem among, guru diharapkan mampu menjadi panutan, motivator, fasilitator, dan bertanggung jawab dalam menciptakan generasi-generasi yang beriman, merdeka lahir batin, mandiri, displin, cerdas, terampil, dan bertanggung jawab atas dirinya, keluarga, dan masyarakat.